(untitled) (Research, Society and Development, 2021)
Milk protein concentrate (MPC) is a commercial designation for dairy ingredients with higher protein and lower lactose content than conventional skim milk powder. Lactose in its amorphous form is found in several spray-dried dairy powders. Amorphous lactose is thermodynamically unstable and can mobilize and crystallize over time under adequate temperature and moisture content. Moisture sorption from the air precedes crystallization, enhancing MPC cohesiveness and caking. This increased humidity results in poor rehydration and dispersibility, lower yield during drying, operation problems, difficulties in handling and storage. Moreover, lactose crystallization in MPC can cause Maillard browning reaction and fat oxidation. To avoid this problem, it is necessary to pre-crystallize lactose as alpha-lactose monohydrate, which is non-hygroscopic, before spray drying. Such a procedure is essential in preventing deterioration of MPC resulting from lactose crystallization or chemical reactions. Additionally, the control of this step is important to obtain specified and reproducible powder, in terms of size and crystallization level. There are various reports on the rheology of milk-based products; however, there is a lack of investigation on concentrated systems. Consequently, the objective of the present work is to review basic concepts of lactose crystallization and rheology of milk protein concentrate.